2015
DOI: 10.1891/0886-6708.vv-d-13-00085
|View full text |Cite
|
Sign up to set email alerts
|

Police Officers’ Attitudes and Challenges With Charging Stalking

Abstract: This study examined 2 groups of police officers on perceived barriers and attitudes related to charging stalking. Police officers who categorized into groups based on if they had (n=73) or had not (n=90) previously charged stalking. Results indicated that officers who had never charged stalking viewed stalking as less dangerous, believed that officers do not file reports when called for stalking, and perceived all barriers related to charging stalking as more challenging than officers who had previously charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 21 publications
(22 reference statements)
0
39
0
Order By: Relevance
“…Advances in technology have created avenues for perpetrators to maintain contact with victims through electronic communication or internet-capable devices (Reyns et al, 2011; Spitzberg, 2016). Stalking is further complicated where the police and victim are working in concert during the investigative process because victims are often relied upon to save and/or maintain evidence (e.g., letters, text messages, voice mail, and other electronic or technological communication) to display a pattern of contact (Lynch & Logan, 2015). This translates to multiple interactions with police, which may frustrate police and inhibit victim cooperation.…”
Section: Police Response To Ipv and Stalkingmentioning
confidence: 99%
See 3 more Smart Citations
“…Advances in technology have created avenues for perpetrators to maintain contact with victims through electronic communication or internet-capable devices (Reyns et al, 2011; Spitzberg, 2016). Stalking is further complicated where the police and victim are working in concert during the investigative process because victims are often relied upon to save and/or maintain evidence (e.g., letters, text messages, voice mail, and other electronic or technological communication) to display a pattern of contact (Lynch & Logan, 2015). This translates to multiple interactions with police, which may frustrate police and inhibit victim cooperation.…”
Section: Police Response To Ipv and Stalkingmentioning
confidence: 99%
“…Limited studies have examined police response to stalking (Brady & Nobles, 2017; Jasinski & Mustaine, 2001; Jordan et al, 2003; Storey & Hart, 2011; Tjaden & Thoennes, 2000) and have noted shortcomings. Police may not recognize stalking behavior or may not fully understand the statute guiding their jurisdiction (Lynch & Logan, 2015). Officers may use alternative offense codes to produce case dispositions that can be applied to a single incident, like harassment or terroristic threat, rather than statutes that capture unwanted pursuit behavior over time (Brady & Nobles, 2017).…”
Section: Police Response To Ipv and Stalkingmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, studies have found that officers make decisions in a downstream orientation in which an arrest depends on the likelihood of prosecutors filing formal charges (Frohmann, 1997;Klein et al, 2009;Lynch & Logan, 2015;Spohn & Tellis, 2019). Prosecutors file charges based on convictability (Albonetti, 1986(Albonetti, , 1987 and thus, the amount of time and resources dedicated to a stalking investigation may be contingent on officers' perceptions of whether prosecutors would accept the case for prosecution.…”
Section: Policing Stalking Complaintsmentioning
confidence: 99%